Design of High-Throughput Screening of Natural Extracts to Identify Molecules Bypassing Primary Coenzyme Q Deficiency in Saccharomyces cerevisiae. (March 2020) - Berenguel Hernández, Aida M.; de la Cruz, Mercedes; Alcázar-Fabra, María; Prieto-Rodríguez, Andrés; Sánchez-Cuesta, Ana; Martin, Jesús; Tormo, José R.; Rodríguez-Aguilera, Juan Carlos; Cortés-Rodríguez, Ana Belén; Navas, Plácido; Reyes, Fernando; Vicente, Francisca; et al.
Coenzyme Q10 (CoQ10 ) deficiency syndrome is a rare disease included in the family of mitochondrial diseases, which is a heterogeneous group of genetic disorders characterized by defective energy production. CoQ10 biosynthesis in humans requires at least 11 gene products acting in a multiprotein complex within mitochondria. The high-throughput screening (HTS) method based on the stabilization of the CoQ biosynthesis complex (Q-synthome) produced by the COQ8 gene overexpression is proven here to be a successful method for identifying new molecules from natural extracts that are able to bypass the CoQ6 deficiency in yeast mutant cells. The main features of the new approach are the combination of two yeast targets defective in genes with different functions on CoQ6 biosynthesis to secure the versatility of the molecule identified, the use of glycerol as a nonfermentable carbon source providing a wide growth window, and the stringent conditions required to mark an extract as positive. The application of this pilot approach to a representative subset of 1200 samples of the Library of Natural Products of Fundación MEDINA resulted in the finding of nine positive extracts. The fractionation of three of the nine extracts allowed the identification of five molecules; two of them are present in molecule databases of natural extracts and three are nondescribed molecules. The use of this screening method opens the possibility of discovering molecules with CoQ10 -bypassing action useful as therapeutic agents to fight against mitochondrial diseases in human patients.